Improving CPAP Adherence in Adults With Obstructive Sleep Apnea Syndrome: A Scoping Review of Motivational Interventions - Rapelli, Giada; Pietrabissa, Giada; Manzoni, Gian Mauro; Bastoni, Ilaria; Scarpina, Federica; Tovaglieri, Ilaria; Perger, Elisa; Garbarino, Sergio; Fanari, Paolo; Lombardi, Carolina; Castelnuovo, Gianluca (Frontiers in Psychology, 2021)
Objective. This scoping review aims to provide an accessible summary of available evidence on the efficacy of motivational interventions to increase adherence to Continuous Positive Airway Pressure (CPAP) among patients with Obstructive Sleep Apnea Syndrome (OSAS) and of their specific aspects and strategies by assessing adherence measures. Methods. A literature search was performed in PubMed, Scopus, Medline, PsycINFO, and Web of Science databases using the concepts of “obstructive sleep apnea syndrome”, “continuous positive airway pressure”, “motivational intervention” and “adherence”. Rigorous inclusion criteria and screening by at least two reviewers were applied. Data were extracted to address the review aims and were presented as a narrative synthesis. Results. Search for databases produced 11 randomized controlled trials, all including naïve CPAP users. Findings showed that motivational interventions were more effective than usual care and educational programs in increasing adherence to CPAP, despite results were not always maintained over time across studies. Discussion. To our knowledge, this is the first scoping review of the literature aimed to explore the characteristics and impact of motivational interventions to promote adherence to CPAP in patients with OSAS. More research providing a detailed description of motivational strategies, and testing of their association with positive treatment outcomes via both direct and indirect measures are needed to increase awareness on active mechanisms of change.